2012
DOI: 10.1371/journal.pone.0035030
|View full text |Cite
|
Sign up to set email alerts
|

The Threonine Protease Activity of Testes-Specific Protease 50 (TSP50) Is Essential for Its Function in Cell Proliferation

Abstract: BackgroundTestes-specific protease 50 (TSP50), a newly discovered threonine enzyme, has similar amino acid sequences and enzymatic structures to those of many serine proteases. It may be an oncogene. TSP50 is up-regulated in breast cancer epithelial cells, and ectopic expression of TSP50 in TSP50-deficient Chinese hamster ovary (CHO) cells has been found to promote cell proliferation. However, the mechanisms by which TSP50 exerts its growth-promoting effects are not yet fully understood.Methodology/Principal F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The cell suspension containing 2000 cells/group were used for soft-agar colony culture assay as previously described [25, 26]. …”
Section: Methodsmentioning
confidence: 99%
“…The cell suspension containing 2000 cells/group were used for soft-agar colony culture assay as previously described [25, 26]. …”
Section: Methodsmentioning
confidence: 99%
“…Yuan et al (12) reported that the overexpression of TSP50 promoted proliferation and migration of cervical cancer cells, depending on its threonine protease activity and its interactions with tumor necrosis factor-α-induced NF-κB. To delineate the involvement of TSP50 in cellular proliferation, Li et al (23) constructed and characterized a mutant TSP50 (TSP50 T310A) whose mutation significantly decreased TSP50-induced cellular proliferation in vitro and abolished the tumorigenicity of TSP50 in nude mice. These results revealed that the T310A mutation prevented interaction between TSP50 and the NF-κB-IκBα complex, which is necessary for TSP50 to perform its function in cellular proliferation.…”
Section: Os ---------------------------------------------------------mentioning
confidence: 99%
“…The cells are also commonly used in the evaluation of exogenous gene function by stably transfecting the targeting genes in vitro and in vivo (Bifulco et al, ; Song et al, ). It is reported that CHO cells are transfected with TSP50 gene to prove the carcinogenic potential of TSP50 (Song et al, ; Li et al, ), which indicates CHO cell line can be used to evaluate the phenotypic characteristics of an exogenous gene (An et al, ). In this study, human basigin gene encoding CD147 was delivered into CHO cells to establish stably transfected CHO cell line under a selective condition.…”
Section: Introductionmentioning
confidence: 99%